Synthesis and Reactions of Borazines - Neogi, Ishita; Szpilman, Alex M. (Synthesis, 2022)
Given the wide array of current applications of borazine-based materials, synthetic access to these compounds is of importance. This review summarizes the many ways of preparing borazines and its carbo-substituted analogues. In addition, the functionalization of borazines is covered. The synthesis of molecules incorporating more than one borazine units as well as aspects of unsymmetrically substituted borazines are not included. The literature has been covered comprehensively until the end of 2020.1 Introduction: Structure and Properties of Borazine2 Synthesis of Parent Borazine3 Synthesis of N-Substituted Borazines4 Synthesis of B-Halo/B-Halo-N-Substituted Borazines5 Synthesis of B-Substituted Borazines6 Synthesis of Polycyclic Borazines Containing One Borazine Ring7 Modifications or Hydrolysis of the Borazine Ring8 Borazine Metal Complexes9 Outlook and Conclusion
Keywords: borazine; aromaticity; synthesis; supramolecular chemistry; boron; nitrogen